Analysis of the absorption spectrum of 12CH4 in the region 5855–6250 cm−1 of the 2ν3 band. (December 2017) - Nikitin, A.V.; Chizhmakova, I.S.; Rey, M.; Tashkun, S.A.; Kassi, S.; Mondelain, D.; Campargue, A.; Tyuterev, Vl.G.
Highlights: 12 CH4 line list at 296 K is theoretically modeled in the 5855–6250 cm −1 region. 3277 12 CH4 experimental line positions are reproduced with a 0.0015 cm −1 rms . 2381 12 CH4 experimental line intensities at 296 K are modeled with 8.1% rms. The new assignments are included in the WKLMC list for natural methane at 296 K. Abstract: Accurate rovibrational analysis of the upper part of the Tetradecad 12 CH4 spectrum in the 5855–6250 cm −1 region is reported for J  ≤ 10. The analysis uses the WKLMC experimental line list previously obtained in Grenoble by Cavity Ring Down Spectroscopy and Differential laser Absorption Spectroscopy at T = 296 K. Based on a previously published ab initio potential energy surface, the full Hamiltonian of methane nuclear motion was reduced to an effective Hamiltonian using high-order Contact Transformation method with a subsequent empirical optimization of parameters. Overall, more than 3200 12 CH4 transitions are assigned adding about 1800 new assignments to those provided in the HITRAN database for 12 CH4 in the region. The 12 CH4 experimental line positions were fitted with RMS standard deviations of 0.0015 cm −1 and 2381 line intensities were modeled using an effective dipole moment with the RMS deviation of 8%. Rovibrational energy levels of sixteen vibrational states of the upper part of the Tetradecad system were determined. For the first time all three sub-levels of the weak 4ν2 band were assigned. As a result, a new version of the WKLMC list for natural methane at 296 K is provided including the new assignments in the 5855–6250 cm −1 region.